Inorganic clay nanocomposite system for improved cholinesterase inhibition and brain pharmacokinetics of donepezil. (2nd January 2020) - Singh, Anurag Kumar; Mishra, Sunil Kumar; Mishra, Gaurav; Maurya, Anand; Awasthi, Rajendra; Yadav, Mukesh Kumar; Atri, Neelam; Pandey, Pawan Kumar; Singh, Santosh Kumar
Abstract: Objective: Brain drug delivery for effective treatment of neurodegenerative disorders is limited due to the selective permeability of blood brain barrier (BBB). During the past few years, development of novel delivery system has attracted considerable attention of formulation scientists to overcome the permeability limitation caused by BBB. Significance: Based on the outcomes of this study and taking into consideration of the unique characteristics of laponite, it can be further explored to deliver many other central nervous system acting drugs. Methods: In the present study, laponite (LAP) nanocomposites were exploited for the improved brain delivery of donepezil (DZ) following encapsulation approach due to their nano-size and positive charge at pH <9. Result: The size of prepared nanocomposites was 53.7 ± 4.0 to 137.7 ± 11.0 nm. The drug was released in a sustained manner till 120 h in phosphate buffer saline (pH 7.4) and acid phthalate buffer (pH 4.0). LAPDZ formulations inhibited acetylcholinesterase approximately by 82%, significantly higher ( p < 0.05) than plain DZ (30%). Swiss albino mice exhibited enhanced brain uptake of LAPDZ administered via intravenous route. Promising pharmacokinetic parameters were observed in animals treated with LAPDZ. LAPDZ formulation showed half-life (t1/2 ), volume of distribution (Vd) and clearance (Cl) as 5.53 ± 0.40 h −1, 0.129 ± 0.02 L, 0.015 ± 0.002 L/h, respectively. While DZ solution showed the same parameters as 1.06 ± 0.12 h −1, 0.168 ± 0.01 L, 0.106 ± 0.013 L/h, respectively. The brain uptake of LAPDZ formulation was improved with quintuplet t1/2 . Conclusion: Based on the results of present study, it is proposed that the formulated nanocomposite would result in improved patient compliance with therapeutic effect at lower doses.